Meaning Of Words A ̅lu in Al-Qur'an: Toshihiko Izutsu's Semantic Analysis - Tawakkal MS, Moch Iqbal; Rhain, Ainur; Dahliana, Yeti (SEAN Institute, 2024)
The word ālu in the Qur'an indicates the meaning of people who have a close relationship or family (Qarabah). The term ālu is mentioned 31 times in the Qur'an. Each verse contained in various surahs certainly has a different meaning, so it requires in-depth understanding. The disclosure of the meaning of ālu will be analyzed by the author using the Qur'anic semantic approach developed by Toshihiko Izutsu. According to Izutsu, Qur'anic semantics is an attempt to reveal the Qur'anic worldview (weltanschauung) through semantic analysis of key vocabulary or terms in the Qur'an. This research process involves investigating the basic meaning and relational meaning of the word ālu using syntagmatic and paradigmatic analysis.